2016
DOI: 10.5114/amsad.2016.60759
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between leukocyte count and infarct size in ST segment elevation myocardial infarction

Abstract: IntroductionRegarding the inflammatory mechanisms involved in ischemic heart disease, currently the leukocyte count is the subject of studies related to its association with the prognosis and mortality of ST segment elevation myocardial infarction (STEMI). Our aim is correlate the leukocyte count rise with the size of STEMI, evaluated with the area under the curve (AUC) and the peak of necrosis markers release.Material and methodsThis study is a sub-analysis of the TETHYS trial, a clinical trial that evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
1
6
0
1
Order By: Relevance
“…The importance of WBC (White Blood Cells) count in patients with myocardial infarction has been described in many studies. In patients with STEMI and NSTEMI, the WBC number is important in the first hours of an acute cardiovascular episode as a prognostic marker for patients undergoing primary percutaneous coronary intervention [20,21]. In our study, we observed a statistically significant higher number of WBC in the STEMI group in comparison to HIV-infected patients.…”
Section: Discussionsupporting
confidence: 53%
“…The importance of WBC (White Blood Cells) count in patients with myocardial infarction has been described in many studies. In patients with STEMI and NSTEMI, the WBC number is important in the first hours of an acute cardiovascular episode as a prognostic marker for patients undergoing primary percutaneous coronary intervention [20,21]. In our study, we observed a statistically significant higher number of WBC in the STEMI group in comparison to HIV-infected patients.…”
Section: Discussionsupporting
confidence: 53%
“…These results are similar to the observations reported by other studies. [14][15][16][17] Raised total leukocyte count is an indicator of inflammation because it acts as a host defence to injury. In CAD, leukocytes not only cause oxidative and proteolytic injury to the coronary arteries but also aggregate and impact the microvasculature thus leading to hypercoagulable state and electrical instability in the heart.…”
Section: Discussionmentioning
confidence: 99%
“…74 It is well known that inflammation plays an important role in ischemia/reperfusion injury of the myocardium. 80,81 Therefore, it has been suggested that the cardioprotective effect of BNP during reperfusion may be a consequence of the limitation of leukocyte infiltration in the infarcted area. Indeed, it turned out that after 2 days of cardiac reperfusion, the number of leukocytes in the infarction zone in BNP-treated rats decreased by 30% (Table 2).…”
Section: Data From Experimental Studiesmentioning
confidence: 99%